Effects of abasic sites and DNA single-strand breaks on prokaryotic RNA polymerases. - Zhou, W (1993)
Abasic sites are thought to be the most frequently occurring cellular DNA damage and are generated spontaneously or as the result of chemical or radiation damage to DNA. In contrast to the wealth of information that exists on the effects of abasic sites on DNA polymerases, very little is known about how these lesions interact with RNA polymerases. An in vitro transcription system was used to determine the effects of abasic sites and single-strand breaks on transcriptional elongation. DNA templates were constructed containing single abasic sites or nicks placed at unique locations downstream from two different promoters and were transcribed by SP6 and Escherichia coli RNA polymerases. SP6 RNA polymerase is initially stalled at abasic sites with subsequent, efficient bypass of these lesions. E. coli RNA polymerase also bypassed abasic sites. In contrast, single-strand breaks introduced at abasic sites completely blocked the progression of both RNA polymerases. Sequence analysis of full-length transcripts revealed that SP6 and E. coli RNA polymerases insert primarily, if not exclusively, adenine residues opposite to abasic sites. This finding suggests that abasic sites may be highly mutagenic in vivo at the level of transcription.